Clazosentan, an endothelin receptor antagonist, in patients with aneurysmal subarachnoid haemorrhage undergoing surgical clipping: a randomised, double-blind, placebo-controlled phase 3 trial (CONSCIOUS-2) - Macdonald, R Loch; Higashida, Randall T; Keller, Emanuela; Mayer, Stephan A; Molyneux, Andy; Raabe, Andreas; Vajkoczy, Peter; Wanke, Isabel; Bach, Doris; Frey, Aline; Marr, Angelina; Roux, Sébastien; et al. (Lancet neurology, 2011)
Clazosentan, an endothelin receptor antagonist, significantly and dose-dependently reduced angiographic vasospasm after aneurysmal subarachnoid haemorrhage (aSAH). We investigated whether clazosentan reduced vasospasm-related morbidity and all-cause mortality. In this randomised, double-blind, placebo-controlled, phase 3 study, we randomly assigned patients with aSAH secured by surgical clipping to clazosentan (5 mg/h, n=768) or placebo (n=389) for up to 14 days (27 countries, 102 sites, inpatient and outpatient settings) using an interactive web response system. The primary composite endpoint (week 6) included all-cause mortality, vasospasm-related new cerebral infarcts, delayed ischaemic neurological deficit due to vasospasm, and rescue therapy for vasospasm. The main secondary endpoint was dichotomised extended Glasgow outcome scale (GOSE; week 12). This trial is registered with ClinicalTrials.gov, number NCT00558311. In the all-treated dataset, the primary endpoint was met in 161 (21%) of 764 clazosentan-treated patients and 97 (25%) of 383 placebo-treated patients (relative risk reduction 17%, 95% CI −4 to 33; p=0·10). Poor functional outcome (GOSE score ≤4) occurred in 224 (29%) clazosentan-treated patients and 95 (25%) placebo-treated patients (−18%, −45 to 4; p=0·10). Lung complications, anaemia, and hypotension were more common with clazosentan. Mortality (week 12) was 6% in both groups. Clazosentan at 5 mg/h had no significant effect on mortality and vasospasm-related morbidity or functional outcome. Further investigation of patients undergoing endovascular coiling of ruptured aneurysms is needed to fully understand the potential usefulness of clazosentan in patients with aSAH. Actelion Pharmaceuticals.